Outcomes of Recurrent Nasopharyngeal Carcinoma Patients Treated With Salvage Surgery: A Meta-Analysis - Feng, Yekai; Dai, Zhimei; Yan, Ruicheng; Li, Feng; Zhong, Xiaosheng; Ye, Haoxin; Chen, Caiqing; Fan, Shaochong; Qing, Cheng; Pan, Yong; Sun, Haiying (Frontiers in Oncology, 2021)
Objective: To assess the efficacy of treatment outcomes of salvage surgery for recurrent nasopharyngeal carcinoma (rNPC). Methods: We conducted a detailed search of the literatures in biomedical databases published from January 1990 to December 2020. The main research features and results of interest were retrieved from the articles that met the selection criteria for meta-analysis. Results: A total of 21 articles with 778 patients were included, 17 of which met the meta-analysis inclusion criteria. The pooled 2-year overall survival (OS), 5-year OS, and 2-year disease-free survival (DFS) were 71%, 50%, and 61%, respectively. Subgroup analysis was conducted with postoperative adjuvant therapy. The pooled 2-year OS, 5-year OS and 2-year DFS of the postoperative adjuvant therapy group compared with the surgery alone group were 69% vs 72%, 44% vs 56%, and 77% vs 54%, respectively. Univariate and multivariate analyses were performed on 178 patients with detailed individual postoperative survival data in 10 articles. On multivariate analysis , recurrent T (RT) stage and adjuvant therapy were independent predictors of outcomes . Conclusions: The meta-analysis indicated that recurrent NPC patients can obtain survival benefits from salvage surgery. Accurately assessing the rT stage of the tumor and choosing the appropriate surgical method are important to the success of the surgery. Although the prognostic factors influencing outcome have been studied, conclusive data on the survival benefits are still lacking. RCTs to compare surgery alone and postoperative adjuvant therapy are needed in patients with positive margin status after salvage surgery.